Social Representations of Autism Among Speech Therapists in Morocco and Their Influence on Communication Support for Children with ASD: A Psychosocial Perspective - ZERROUK Zineb (African Scientific Journal, 2025)
Abstract This article investigates the social representations of Autism Spectrum Disorder among speech therapists in Morocco and examines how these representations shape their communication support practices. Despite the increasing prevalence of Autism Spectrum Disorder, public health and educational responses remain limited in the Moroccan context. Grounded in Moscovici's theory of social representations, this study adopts a mixed-methods approach to identify the ways in which speech therapists perceive and label autism and assesses whether and how these perceptions influence their professional behaviors. The research sample consists of 80 speech-language pathologists working in both the public and private sectors, selected based on their relevance to the research problem. The analysis reveals a discordance between predominantly negative representations and the reported use of communication strategies that align with international best practices. This contradiction calls attention to the implicit frameworks guiding therapeutic engagements and raises implications for policy and training reforms. Keywords: Social Representations, Autism Spectrum Disorder, Speech Therapy, Professional Practice, Morocco, Communication Support